Sodium-alginate biopolymer as a template for the synthesis of nontoxic red emitting Mn2+-doped CdS nanoparticles. Issue 84 (21st November 2017) - Kuzmanović, M.; Božanić, D. K.; Milivojević, D.; Ćulafić, D. Mitić; Stanković, S.; Ballesteros, C.; Gonzalez-Benito, J.
Abstract : Structural and optical characteristics of manganese doped cadmium sulfide nanoparticles prepared by in situ chemical synthesis using biocompatible Na-alginate biopolymer as a template is reported. Abstract : Manganese-doped cadmium sulfide (CdS:Mn) nanoparticles were prepared by chemical synthesis using sodium-alginate as template. The preparation of the nanocomposites involved ionic crosslinking of the biopolymer by dimerization of its α-l -guluronic monomers with Cd 2+ and subsequent formation of the semiconductor nanoparticles upon addition of sulfide ions in the presence of Mn 2+ . The crystalline phase of CdS in the material was confirmed by XRD. The surface morphology of the nanocomposites was investigated by SEM. The observation by TEM showed that the CdS:Mn particles were spherical in shape with diameters of approximately 4 nm. EPR measurements of the CdS:Mn-alginate nanocomposite showed that the Mn 2+ ions were incorporated in cationic sites of CdS with lower symmetry. Due to a distorted crystal field induced by the Mn 2+ ions, photoluminescence spectra of the CdS:Mn-alginate showed red fluorescence between 650 nm and 750 nm falling into the optical window for bioimaging in which the light has its maximum tissue penetration depth. It was demonstrated that the interaction between the nanoparticles and the matrix prevents release of CdS into the environment, leading to low acute toxicity of the nanocomposites.